Counseling in fetal medicine: evidence‐based answers to clinical questions on morbidly adherent placenta. (4th March 2016) - D'Antonio, F.; Palacios‐Jaraquemada, J.; Lim, P. S.; Forlani, F.; Lanzone, A.; Timor‐Tritsch, I.; Cali, G.
Abstract: Although the incidence of morbidly adherent placenta (MAP) has risen progressively in the last two decades, there remains uncertainty about the diagnosis and management of this condition. The aim of this review is to provide up‐to‐date and evidence‐based answers to common clinical questions regarding the diagnosis and management of MAP. Different risk factors have been associated with MAP; however, previous Cesarean section and placenta previa are the most frequently associated. Ultrasound is the primary method for diagnosing MAP and has a good overall diagnostic accuracy for its detection. When considering the different ultrasound signs of MAP, color Doppler seems to provide the best diagnostic performance. Magnetic resonance imaging has the same accuracy in diagnosing MAP as does ultrasound examination; its use should be considered when a resective procedure, such as hysterectomy, is planned as it can provide detailed information about the topography of placental invasion and predict difficulties that may arise in surgery. The optimal gestational age for delivery in pregnancies with MAP is yet to be established; planning surgery between 35 and 36 weeks of gestation provides the best balance between fetal maturity and the risk of unexpected episodes of heavy bleeding, which are more likely to occur with delivery after this timepoint, especially in severe cases of MAP. The optimal surgical approach to MAP depends on multiple factors, including availability of an experienced team, specific surgical skills and hospital resources. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.